DETERMINANTS OF FOREIGN DIRECT INVESTMENT IN ORGANIZATION OF ISLAMIC COOPERATION COUNTRIES IN ASEAN: EMPIRICAL EVIDENCE OF VECTOR ERROR CORRECTION MODEL - M. Iqbal; Syahrul Gunawan; Ajeng Lestari; Abdullah Abdullah; Azizan Hadi (Fakultas Ekonomi Dan Bisnis Islam IAIN Metro, 2025)
This study examines the factors that influence FDI in OIC member countries in the ASEAN region: Indonesia, Malaysia, and Brunei Darussalam. Foreign direct investment is considered an important source of capital for the economic growth of developing countries. FDI flows to developing countries reached USD 837 billion in 2021, with Southeast Asia being one of the largest recipients. This study uses time series data from 2000–2022 and a VECM model to analyze the causal relationship between FDI, exchange rates, inflation, CO₂ emissions, exports, and imports. The results show that exchange rates and inflation have a significant impact on foreign direct investment in the long term, while CO₂ emissions, exports, and imports are not significant, differing from some previous studies that emphasized the role of trade and the environment. These findings indicate that macroeconomic stability, regulation, infrastructure, and institutions are key determinants of FDI flows. Although the impact of green policies has not been significant, initiatives such as carbon taxes and clean energy programs in the three countries show potential for attracting sustainable investment in the future.